The role of monitoring and evaluation to ensure functional access to community-based early diagnosis and treatment in a malaria elimination programme in Eastern Myanmar. - Rae, JD; Nosten, S; Proux, S; Myint Thu, A; Cho, WC; Paw, K; Paw, ES; Shee, PB; Be, SA; Dah, SH; Moo, SKL; Minh, SMC; et al. (BioMed Central, 2019)
Background: Improving access to early diagnosis and treatment (EDT) has increasingly proven to be a major contributor to decreasing malaria incidence in low-transmission settings. The Malaria Elimination Task Force (METF) has deployed malaria posts set up in Eastern Myanmar, providing free uninterrupted community-based access to EDT in more than 1200 villages. Ensuring high quality services are provided by these malaria posts is essential to reaching elimination targets. The present study aimed to determine the functionality of the malaria posts in the METF programme. Methods: This report analysed routinely collected data (weekly reports, individual consultation, diagnostic test quality control) and data collected specifically during monitoring and evaluation visits using descriptive statistics and univariate logistic regression. The presence of major dysfunctions (stock-outs and reported closing; likely to impair the ability of the population to access EDT) or minor dysfunctions (no formal METF training, lack of regular salary, forms and manual not on-site, and low frequency of supervisor visits) and the ability to anticipate dysfunctions through analysis of weekly reports were assessed. Results: A total of 65% of malaria posts had no major dysfunction identified during monitoring and evaluation visits, while 86% of malaria posts were fully stocked with tests and medicines used for treatment. Diagnosis was correctly conducted with few false positives and rare mis-speciation of results. Malaria post worker knowledge of malaria treatments showed few gaps, mostly in the treatment of more complex presentations. Malaria posts were well utilized in the population, with 94% of consultations occurring within the first 3 days of fever. In the regression analysis, reported stock-outs and delayed weekly reports were associated with observed major and minor dysfunctions in monitoring and evaluation visits, emphasizing the need to reinforce support to malaria post supervisors, who were responsible for the local logistics of supply and data transmission and day-to-day supervision. Conclusion: The malaria posts operating under the METF programme perform to a high standard, with the majority offering uninterrupted access to diagnosis and treatment, and high service uptake in the villages serviced by the programme. However, programme operations can be strengthened by increasing malaria post supervisor visits and re-training malaria post workers.